1961
DOI: 10.1039/jr9610002066
|View full text |Cite
|
Sign up to set email alerts
|

393. Sulphur chloride pentafluoride: reaction with unsaturated hydrocarbons

Abstract: Sulphur chloride pentafluoride adds to certain olefins and chloro-olefins to give 2-chloroalkylsulphur pentafluorides ; acetylene and propyne give 2-chlorovinyl-and 2-chloropropenyl-sulphur pentafluoride, respectively. These products eliminate hydrogen chloride on treatment with potassium hydroxide, to give pentafluorosulphur-substituted olefins and acetylenes. SULPHUR CHLORIDE PENTAFLUORIDE does not react with paraffin hydrocarbons, but when heated under moderate pressures with certain olefins and chloro-olef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…It has been shown that SF 5 X (X ¼ Cl, Br) will add to alkynes; SF 5 Cl was added to acetylene and propyne [5] and to RCBCOR 0 (R¼CH 3 , H; R 0 ¼CH 3 , CH 3 CH 2 ) [6,7] while in separate reports, SF 5 Br was added to YCBCH (Y ¼ SF 5 , CF 3 ) and to CF 3 CBCH or CH 3 CBCH [8,9]. In all cases, the SF 5 group was attached to the olefinic carbon with the most hydrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that SF 5 X (X ¼ Cl, Br) will add to alkynes; SF 5 Cl was added to acetylene and propyne [5] and to RCBCOR 0 (R¼CH 3 , H; R 0 ¼CH 3 , CH 3 CH 2 ) [6,7] while in separate reports, SF 5 Br was added to YCBCH (Y ¼ SF 5 , CF 3 ) and to CF 3 CBCH or CH 3 CBCH [8,9]. In all cases, the SF 5 group was attached to the olefinic carbon with the most hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…While a significant number of fluorinated acrylates are known only a limited number containing the SF 5 -group have been reported. In all but one of the cases, the SF 5 -group is located in the alcohol portion of the acrylate ester.…”
Section: Introductionmentioning
confidence: 99%
“…With organic alkenes, SF 5 Cl reacts both photochemically and thermally. 112 It is a common feature of the chemistry of SF 5 X to proceed via SF 5 • radicals and a …”
Section: Sulfur Hexafluorides and Derivativesmentioning
confidence: 99%
“…6 To the start of this work, syntheses of some compounds with pentafluorosulfanyl group have been reported. 7 At the same time, the preparation of F 5 S-substituted dienes with terminal CH 2 -group, to the best of our knowledge, has not been described hitherto.…”
Section: Synthesis Of Unsaturated Compounds Containing Pentafluorosulmentioning
confidence: 99%